What's the matter with Delaware? : how the first state has favored the rich, powerful, and criminal-and how it costs us all - Weitzman, Hal, 1972- (Princeton, New Jersey : Princeton University Press, 2022)
"Delaware is so boring that it's funny, as immortalized by one of the most memorable jokes in the movie Wayne's World. Indeed, Delaware is the de facto capital of corporate America, the embodiment of blandness. But what if behind this banality lay a systematic enterprise that blatantly diverted public funds away from the poorest people in America and supported the worst criminals and dictators in the world? Legal scholars, financial journalists, and elite businesspeople will all tell you that by now it's common knowledge that Delaware is not just business friendly-it is an obvious financial haven for terrorists, criminals, dictators, arms-dealers, money-launderers, and tax evaders. But no one has put all the pieces together and written a book about it. Accomplished investigative journalist Hal Weitzman does just that. This book explains in clear terms to the broadest possible audience how Delaware diverts money from the poorest states in the US through various means, most obviously the "Delaware loophole," which in effect enables huge businesses such as Home Depot and WalMart to avoid paying state taxes to the states in which they actually conduct business. In Shut Down Delaware, Weitzman will also show how Delaware is an integral part of an international system that fosters extraordinary tax evasion and money laundering, through its indefensible system of incorporation, which allows anyone to set up a business without specifying who owns the business. Over time what this has led to is that some of the biggest and most well-known businesses in the world sharing the same Delaware addresses as the world's most notorious arms dealers and dictators. Using public data, interviews, investigative journalism, and academic scholarship, Weitzman will be the first to put the story together in book form and call the industry out. For years, US lawmakers and law enforcement have been criticizing foreign tax havens such as Switzerland and Luxembourg for unjust practices, but when the trail inevitably leads back to Delaware, there is nothing more they can say or do. Shut Down Delaware will bring this glaring discrepancy to light, and the implications could be tremendous. First, there is no defense for Delaware allowing business incorporation without any identification. Second, many states have gotten wise and passed legislation preventing businesses from taking advantage of the "Delaware loophole" but most, including the nation's poorest states, have not. A high-profile book could be just what it takes raise public awareness on both fronts, and if these laws were changed, a huge amount of business would be affected. Shut Down Delaware has the potential to create an enormous shift in the way the world's largest companies and shadiest illegal entities do business in the United States"--
"How the "First State" has enabled international crime, sheltered tax dodgers, and diverted hard-earned dollars from the rest of usThe legal home to over a million companies, Delaware has more registered businesses than residents. Why do virtually all of the biggest corporations in the United States register there? Why do so many small companies choose to set up in Delaware rather than their home states? Why do wealthy individuals form multiple layers of private companies in the state? This book reveals how a systematic enterprise lies behind the business-friendly corporate veneer, one that has kept the state afloat financially by diverting public funds away from some of the poorest people in the United States and supporting dictators and criminals across the world. Hal Weitzman shows how the de facto capital of corporate America has provided safe haven to money launderers, kleptocratic foreign rulers, and human traffickers, and facilitated tax dodging and money laundering by multinational companies and international gangsters. Revenues from Delaware's business-formation industry, known as the Franchise, account for two-fifths of the state's budget and have helped to keep the tax burden on its residents among the lowest in the United States. Delaware derives enormous political clout from the Franchise, effectively writing the corporate code for the entire country-and because of its outsized influence on corporate America, the second smallest state in the United States also writes the rules for much of the world.What's the Matter with Delaware? shows how, in Joe Biden's home state, the corporate laws get written behind closed doors, enabling the rich and powerful to do business in the shadows"--
Introduction. The mother of trusts -- Enjoy Delaware® -- The Delaware loophole -- Delaware has our money -- Delaware is everywhere -- Colonial origins -- A very Delawarean lynching -- The process : how the corporate code is made -- Don't screw it up -- Uncle Dupie -- In good standing -- Conclusion: No more hiding in plain sight.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 31, 2022).
JSTOR
Keywords: Tax havens -- United States; Corporations -- Taxation -- United States; Money laundering -- United States; Corporation law -- Delaware; Taxation -- Delaware; Finance -- Delaware; Delaware -- Economic policy; Paradis fiscaux -- États-Unis.; Sociétés -- Impôts -- États-Unis.; Blanchiment de l'argent -- États-Unis.; Impôt -- Delaware; Finances -- Delaware; Delaware -- Politique économique.; Sociétés -- Droit -- Delaware -- Législation.; BUSINESS & ECONOMICS / Finance / General; POLITICAL SCIENCE / Public Policy / Economic Policy; BUSINESS & ECONOMICS / Finance; Corporation law; Corporations -- Taxation; Economic policy; Finance; Money laundering; Tax havens; Taxation; Delaware; United States; Electronic books